2010
DOI: 10.1136/ard.2009.124586
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bone resorption blunts osteoarthritis in mice with high bone remodelling

Abstract: These findings support the hypothesis that the level of bone resorption influences cartilage metabolism and that inhibition might prevent the progression of OA. Targeting bone resorption might therefore provide an approach to the treatment of high bone resorbing forms of OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 36 publications
4
56
0
Order By: Relevance
“…In experimental studies, OS and ES are also higher in osteoarthritic joints 30 . Inhibiting bone resorption in surgically induced OA mice protects against cartilage degeneration, which is most likely due to the coupling between formation and resorption in bone remodelling 31 . In rats, it has been shown that pre-emptive alendronate treatment before surgically induced OA almost completely prevented the loss of cartilage pointing towards bone tissue playing a major role in OA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies, OS and ES are also higher in osteoarthritic joints 30 . Inhibiting bone resorption in surgically induced OA mice protects against cartilage degeneration, which is most likely due to the coupling between formation and resorption in bone remodelling 31 . In rats, it has been shown that pre-emptive alendronate treatment before surgically induced OA almost completely prevented the loss of cartilage pointing towards bone tissue playing a major role in OA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one of the most commonly used antiresorptive agents, bisphosphonate, may influence periarticular bone changes in OA and could have an effect on the course of the disease, including the possibility of slowing its development and progression [6]. Alendronate, a nitrogen-containing bisphosphonate, has the effect of reducing bone turnover in postmenopausal osteoporosis by inhibiting the differentiation and recruitment of osteoclasts and reducing the activity of the resorptive cells at the level of the remodeling unit [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is now generally recognized that OA is a complex multifactorial disease process involving the whole synovial joint, including articular cartilage, subchondral bone, synovium, and tendons. Increased bone remodeling is a frequent finding in studies of OA joints, thus, subchondral bone turnover has attracted attention with antiresorptives, such as estrogen and bisphosphonates, representing potentially disease-modifying therapies [3,4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…Bisphosphonates alone (e.g., alendronate, risedronate, and pamidronate) or in select combinations with nonsteroidal antiinflammatory drugs (risedronate and meloxicam) have further shown to preserve the periarticular-trabecular bone mass and reduced the formation of both osteophytes and bone marrow lesions in various murine models of OA [18][19][20]. Recently, early alendronate treatment showed complete prevention of both subchondral bone loss and cartilage surface erosions in ovariectomized rats.…”
Section: Animal Studiesmentioning
confidence: 97%